An Albertian View of Buchanan's Contractarianism - Geoffrey Brennan; Hartmut Kliemt (Homo Oeconomicus, 2022)
This paper in honor of Hans Albert '@100' seeks to show how adhering to critical rationalist 'economic philosophy' avoids contradictions in James Buchanan's contractarianism: restricting constitutional economic advice to what serves the ends of all potential addressees simultaneously Buchanan not only blurs the borderline between value-neutral economic philosophy and substantive moral philosophy but also contradicts his thesis of the "necessary relativism and individualism of values". Translating 'means-ends'-relations into technological 'cause-effect'-relations, Albert can treat technological blueprints as nomological hypotheses subject to scientific test and corroboration while leaving their practical implementation to citizens whose contingent particular ends may or may not be universalistic.
Keywords: A12; B41; D61; 330; Critical rationalism; Contractarianism; Value-neutrality of economics; Value-neutrality of economic advice; H. Albert; Buchanan; Sugden; Vanberg